2023
DOI: 10.1097/txd.0000000000001476
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Kidney Donor Profile Index and 1-y Graft Function

Abstract: Background. The association between Kidney Donor Profile Index (KDPI) and 1-y estimated glomerular filtration rate (eGFR) with long-term kidney graft survival is well known. Yet, the association between KDPI and 1-y eGFR remains uncertain considering the several concurrent competing risk factors. Methods. This single-center, retrospective cohort study analyzed data from 3059 consecutive deceased donor kidney transplant recipients with a 1-y follow-up from January 2013 to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…4,5 In our country, the mean proportion of transplants with ECD kidneys is around 26.8%, and the use of SCS remains predominant despite the high incidence of DGF of 54%, ranging from 29.9% to 87.7%. 6,7 A national trial demonstrated that machine perfusion significantly reduced DGF incidence, albeit with cost considerations. 8,9 In the context of limited resources and budget constraints, a pharmacoeconomic analysis explores the cost-effectiveness (CE) of implementing HMP specifically for preserving kidneys recovered from ECD.…”
mentioning
confidence: 99%
“…4,5 In our country, the mean proportion of transplants with ECD kidneys is around 26.8%, and the use of SCS remains predominant despite the high incidence of DGF of 54%, ranging from 29.9% to 87.7%. 6,7 A national trial demonstrated that machine perfusion significantly reduced DGF incidence, albeit with cost considerations. 8,9 In the context of limited resources and budget constraints, a pharmacoeconomic analysis explores the cost-effectiveness (CE) of implementing HMP specifically for preserving kidneys recovered from ECD.…”
mentioning
confidence: 99%